Murder Strategy to Improve Students Understanding of PAI in the SMAN Mojoagung - Emi Lilawati; Fitria Dwi Cahyani (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
If we look at the current state of education, we can see that the reality of our education today is far from hopeful. In addition to the need to expand educational opportunities, in terms of quality, there are still many aspects that must be improved. The problem behind this research is that teachers in carrying out learning have not fully used learning strategies and models tailored to the way students learn. This can cause problems when teachers apply monotonous learning strategies and models and there is no conformity with their students' learning style, until ultimately the learning process is less interested in students' learning, so students have difficulty understanding the materials taught. The problems in this study are: How to apply MURDER learning strategy to improve students' understanding of PAI Material at SMAN Mojoagung Jombang and How the level of mastery of student understanding in PAI material at SMAN Mojoagung Jombang by applying MURDER Learning Strategy. In the learning process researchers use PAI subjects as materials or research objects. The subject of this study was a grade XI student of MIPA 3 SMAN Mojoagung Jombang. The approach used in this study is qualitative approach, namely